Different subfamilies of alphoid repetitive DNA are present on the human and chimpanzee homologous chromosomes 21 and 22. - Jørgensen, A L (1987)
The alphoid repeat DNA on chimpanzee chromosome 22 was compared with alphoid repeat DNA on its human homologue, chromosome 21. Hybridization of different alphoid probes under various conditions of stringency show that the alphoid repeats of chimpanzee chromosome 22 are not closely related to those of human chromosome 21. Sequence analysis of cloned dimer and tetramer EcoRI fragments from chimpanzee chromosome 22 confirm the low overall level of homology, but reveal the presence of several nucleotide changes which are exclusive to the chromosome 21 subfamily of human alphoid DNA. Southern blot analysis of alphoid repeat DNA on the chimpanzee X chromosome suggests this subfamily has been strongly conserved during and since the separation of chimpanzee and man although the two subfamilies can be distinguished on the basis of Taq I restriction fragments.